(untitled) (Politeja, 2023)
IM-PRINTED: THE SPECIFICITY OF POST-MEMORY WORK IN WITOLD ZARĘBA’S GRAPHIC COMPOSITION NON OMNIS MORIAR The text provides an analysis of Witold Zaręba’s graphic composition Non omnis moriar. This artistic project draws upon photographs spanning the years 1860 to 1918, postcards used during wartime, or preserved fragments of Austro- Hungarian army uniforms. Through these elements, the artist weaves a visual narrative about the world extending between a soldier’s duty and the compassion exhibited by the nursing sisters attending to the wounded on the World War I fronts. The analysis of Zaręba’s project is approached from three perspectives: a particular interpretation of Marianne Hirsch’s concept of postmemory, the notion of “memory acts” as proposed by Constantine de Saint-Laurent, and the idea of counter-monument as expounded by James E. Young. The intended outcome of this analysis is to address the question of how an artist assumes the role of an “heir” while simultaneously becoming a “worker of memory.” Furthermore, the study seeks to identify an alternative approach to commemoration that deviates from the prevalent forms of monumentalized remembrance observed within public space.